Cross sectional study for contraceptive practices in antenatal women at tertiary rural institute - Divedi, Pragati; Rawat, Rajani; Vishwakarma, Soniya; Mittal, Nupur; Dwivedi, Deepti (International Journal of Research in Medical Sciences, 2018)
Background: Objective of the study was to assess the awareness and acceptance for contraceptive practices amongst the women attending the routine antenatal outpatient services at our tertiary rural institute. Methods: It was a cross sectional study done in UP University of Medical Sciences (UPUMS) Saifai. Three hundred fifty (350) patients aged between 18 -40 years were enrolled in the study after written informed consent. A self structured pre formed questionnaire was provided regarding demographic profile, obstetric profile, contraceptive practices and reasons for not using any contraception. Then data were analysed statistically. Results: Majority of the women were between the age group of 30-35 years and had basic level of education. In our study 90% women were aware of one or more methods of contraception. 86.5% accepted the contraceptive practices and 81.43% followed the contraception. 81.43% used temporary methods of which OCPs, IUCDs, and Condoms were common. Conclusions: Majority of the women were between 30-35 years of age. 90% women knew about some method of contraception. 81.4% women followed the temporary method of contraception. Among non users the main reason for not using contraceptive method were mainly lack of knowledge and they wanted more children.